1978
DOI: 10.1037/0022-0167.25.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Sex and career decision-making styles.

Abstract: Three studies are reported testing the hypothesis of greater reliance on the Intuitive style by females and on the Planning style by males in making career decisions. There were no sex differences in these high school and college samples for stage or style of decision making, vocational self-concept crystallization, or self-rated vocational decisiveness. The Planning style was most highly associated with vocational decisiveness, the third or Choice stage of choosing an occupation, and with stronger Super work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 8 publications
3
34
2
Order By: Relevance
“…Past research has shown that the behaviors studied here correlate positively with the effectiveness of career decision-making (Blustein, 1987;Lunneborg, 1978;Phillips & Strohmer, 1982;Phillips, Pazienza, & Ferrin, 1984;Phillips, Pazienza, & Walsh, 1988;Rubinton, 1980;. The current study demonstrates that these behaviors reflect the basic motivational goals of autonomy in thought and action, of understanding and accepting the self, and/or of striving for success according to social standards.…”
Section: Discussionmentioning
confidence: 70%
“…Past research has shown that the behaviors studied here correlate positively with the effectiveness of career decision-making (Blustein, 1987;Lunneborg, 1978;Phillips & Strohmer, 1982;Phillips, Pazienza, & Ferrin, 1984;Phillips, Pazienza, & Walsh, 1988;Rubinton, 1980;. The current study demonstrates that these behaviors reflect the basic motivational goals of autonomy in thought and action, of understanding and accepting the self, and/or of striving for success according to social standards.…”
Section: Discussionmentioning
confidence: 70%
“…Two career-indecision instruments have been developed in which several factors of career indecision were empirically derived (Career Decision Scale, Osipow, Carney, Winer, Yanico, & Koschier, 1976; Vocational Decision Scale, L. K. Jones & Cheney, 1980). Moreover, researchers also have turned their attention to the relation of career indecision to a host of personality variables such as anxiety (e.g., Hawkins, Bradley, & White, 1977;Mitchell & Krumboltz, 1984), vocational identity (e.g., Holland & Holland, 1977), career decision making styles (e.g., Lunneborg, 1978), and perceptions of problem solving (e.g., Larson & Heppner, 1985). Holland and Holland (1977) expanded the career-indecision research by suggesting that career-undecided students might be conceptualized as a heterogeneous group consisting of multiple subtypes.…”
mentioning
confidence: 99%
“…For instance, a rational decision-making style has been found to be associated with career maturity (Blustein, 1987;Dilley, 1965), planning and information gathering (Jepsen, 1974), ego identity (Blustein & Phillips, 1990), career decisiveness (Lunneborg, 1978;Mau, 1995), problem solving efficacy (Heppner, 1978;Phillips, Pazienza, & Ferrin, 1984a), and occupational certainty (Mau & Jepsen, 1992). In contrast, a nonrational decision-making style tends to be inversely related to progress in resolving various career tasks (Blustein & Phillips, 1990;Mau & Jepsen, 1992;Osipow & Reed, 1985).…”
mentioning
confidence: 99%